2023
DOI: 10.3389/fendo.2023.1119427
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid induced bone disorders in children: Research progress in treatment mechanisms

Abstract: Long-term or supra-physiological dose of glucocorticoid (GC) application in clinic can lead to impaired bone growth and osteoporosis. The side effects of GC on the skeletal system are particularly serious in growing children, potentially causing growth retardation or even osteoporotic fractures. Children’s bone growth is dependent on endochondral ossification of growth plate chondrocytes, and excessive GC can hinder the development of growth plate and longitudinal bone growth. Despite the availability of drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 130 publications
0
2
0
Order By: Relevance
“…This phenomenon most probably is explained by the fact that a significant proportion of patients with PF sustained fractures before LT, and thus corticosteroids were avoided in these children, since steroids may increase the risk for PF. 20 This said, current evidence about corticosteroid use and PF is scarce in the pediatric population. Interestingly, a prospective study from 2011 showed that BMD beyond 1 year post-LT was not influenced by corticosteroid exposure, 10 opening the question of bone recuperation after LT.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…This phenomenon most probably is explained by the fact that a significant proportion of patients with PF sustained fractures before LT, and thus corticosteroids were avoided in these children, since steroids may increase the risk for PF. 20 This said, current evidence about corticosteroid use and PF is scarce in the pediatric population. Interestingly, a prospective study from 2011 showed that BMD beyond 1 year post-LT was not influenced by corticosteroid exposure, 10 opening the question of bone recuperation after LT.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…have been incorporated into different hydrogels to promote wound healing. However, chronic wounds caused by oral mucosal diseases may face challenges when using these drugs, which can have long-term side effects and are costly ( D'Achille and Morroni, 2023 ; Hua et al, 2023 ). Accordingly, we propose to introduce a biomaterial that contains natural active ingredients, it can closely suit the affected area, resists fluid washing and oral movements, exerts an anti-inflammatory effect, and promotes tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%